2021
DOI: 10.1080/21655979.2021.1963908
|View full text |Cite
|
Sign up to set email alerts
|

miR-195-5p regulates cell proliferation, apoptosis, and invasion of thyroid cancer by targeting telomerase reverse transcriptase

Abstract: In most human primary cancers, the expression, or telomerase activity, of telomerase reverse transcriptase (TERT) is detectable. However, the mechanism ofTERTactivity within oncogenesis of thyroid cancer remains largely unknown. In this study, we identified miR-195-5p as having involvement in cell proliferation, apoptosis, and invasion in human thyroid cancer. MTT was used to measure cell proliferation, Transwell chamber was used to measure invasion. Western blotting was used to detect the expressions of TERT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“… 32 Additionally, it has been reported that ncRNA can regulate TERT expression in cancer; however, it is still unclear whether TERT promoter mutations can influence ncRNA regulation. 29 The evidence indicates that ncRNA might be a novel prospect of TERT promoter mutation research in HCC. Since TERT promoter mutations are located in the noncoding part, relative sequencing data are lacking in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Additionally, it has been reported that ncRNA can regulate TERT expression in cancer; however, it is still unclear whether TERT promoter mutations can influence ncRNA regulation. 29 The evidence indicates that ncRNA might be a novel prospect of TERT promoter mutation research in HCC. Since TERT promoter mutations are located in the noncoding part, relative sequencing data are lacking in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hsa-miR-195-5p works as a tumor suppressor in thyroid cancer by targeting TERT mRNA. 29 On the other hand, many studies failed to observe significant correlations between TERT promoter mutations and increased TERT expression. [12][13][14] It has been reported that the increase in TERT expression is not significant in HCC samples with TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V-FITC and Propidium Iodide were mixed into cells and incubated in the dark for 15 minutes. Finally, flow cytometry was used to detect cell apoptosis [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 B-C). Interestingly, hsa-miR-195-5p has been endowed with putative tumor suppressor functions in thyroid cancer, as it inhibits cell proliferation and invasion in thyroid cancer cell lines, while promoting apoptosis [ 8 ]. The most up-regulated miRNA in the TERT promoter mutated FTCs, hsa-miR-200b-3p, has been shown to be down-regulated in anaplastic thyroid carcinoma (ATC)—but little is known regarding the roles of this miRNA in WDTCs [ 9 ].…”
mentioning
confidence: 99%
“…In this pilot series, we demonstrate that TERT promoter mutated FTCs carry a unique miRNA signature and highlight a number of interesting candidates for future studies in terms of disease progression and prognosis. The observed down-regulation of hsa-miR-195-5p should be of particular interest for future studies, as this miRNA could constitute a potent tumor suppressor in thyroid cancer cell lines by targeting TERT mRNA [ 8 ]. Moreover, cancer-related mRNA targets of the differentially expressed miRNAs were amassed in cell cycle and P53 signaling, providing a possible link between TERT promoter mutations and dysregulation of these pathways in FTCs.…”
mentioning
confidence: 99%